Strategy to Accelerate Halal Certification for MSEs in Indonesia: An Analytic Network Process Approach - Widigdo, Aslam Mei Nur; Bayinah, Ai Nur (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2023)
Abstract. The implementation of halal certification in Indonesia by Micro and Small Enterprises (MSEs) is still low, even though there are mandatory provisions according to Law no. 33 of 2014 and there is a free halal certification program(SEHATI). This study aims to analyze the problems faced by the micro and small business sectors in implementing halal certification and formulate strategies to accelerate the implementation of halal certification. The research used the ANP (Analytic Network Process) framework. The data was obtained from interviews with seven expert respondents representing academics, practitioners, the Indonesian Ulama Council, and regulators. The results showed that the strategy that can be formulated to accelerate halal certification for the MSE sector is to combine three alternative strategies in the rder of priority, starting from simplifying the business process of the halal certification submission system, increasing the capability of MSE entrepreneurs, and finally increasing institutional synergy Abstrak. Penerapan sertifikasi halal di Indonesia oleh Usaha Mikro dan Kecil masih rendah, walaupun sudah ada ketentuan wajib sesuai Undang-Undang No. 33 tahun 2014 dan adanya program sertifikasi halal gratis (SEHATI). Penelitian ini bertujuan untuk menganalisis permasalahan yang dihadapi oleh sektor usaha mikro dan kecil dalam menerapkan sertifikasi halal serta merumuskan strategi akselerasi penerapan sertifikasi halal. Penelitian ini menggunakan kerangka ANP (Analytic Network Process). Data diperoleh berdasarkan wawancara dengan tujuh responden pakar yang mewakili akademisi, praktisi, MUI dan regulator. Hasil penelitian menunjukkan bahwa strategi yang dapat diformulasikan untukmengakselerasi sertifikasi halal bagi sektor UMK adalah menggabungkan tiga alternatif strategi dengan urutan prioritas di mulai dari penyederhanaan proses bisnis sistem pengajuan sertifikasi halal, peningkatan kapabilitas pengusaha UMK dan terakhir peningkatan sinergi antar lembaga.